A weak convergence theorem for common fixed points of some generalized nonexpansive mappings and nonspreading mappings in a Hilbert space - Dhompongsa S. (2014)
We study the iterative methods for approximation of fixed points of some generalized nonexpansive mappings and nonspreading mappings in a Hilbert space. Consequently, we obtain the weak convergence theorem for common fixed points of two such mappings. © 2011 Taylor & Francis.